Mathematical modeling clarifies the paracrine roles of insulin and glucagon on the glucose-stimulated hormonal secretion of pancreatic alpha- and beta-cells - Brown, Aedan; Tzanakakis, Emmanuel S. (Frontiers in Endocrinology, 2023)
Blood sugar homeostasis relies largely on the action of pancreatic islet hormones, particularly insulin and glucagon. In a prototypical fashion, glucagon is released upon hypoglycemia to elevate glucose by acting on the liver while elevated glucose induces the secretion of insulin which leads to sugar uptake by peripheral tissues. This simplified view of glucagon and insulin does not consider the paracrine roles of the two hormones modulating the response to glucose of aand b-cells. In particular, glucosestimulated glucagon secretion by isolated α-cells exhibits a Hill-function pattern, while experiments with intact pancreatic islets suggest a 'U'-shaped response. To this end, a framework was developed based on first principles and coupled to experimental studies capturing the glucose-induced response of pancreatic aand b-cells influenced by the two hormones. The model predicts both the transient and steady-state profiles of secreted insulin and glucagon, including the typical biphasic response of normal b-cells to hyperglycemia. The results underscore insulin activity as a differentiating factor of the glucagon secretion from whole islets vs. isolated α-cells, and highlight the importance of experimental conditions in interpreting the behavior of islet cells in vitro. The model also reproduces the hyperglucagonemia, which is experienced by diabetes patients, and it is linked to a failure of insulin to inhibit α-cell activity. The framework described here is amenable to the inclusion of additional islet cell types and extrapancreatic tissue cells simulating multi-organ systems. The study expands our understanding of the interplay of insulin and glucagon for pancreas function in normal and pathological conditions.